Polycystic Ovary Syndrome - Nikthew, Nikoloudakis (Journal of Contemporary Medical Practice, 2025)
This article provides a comprehensive overview of Polycystic Ovary Syndrome PCOS, a common endocrine disorder in women. It explores the causes, symptoms, diagnosis, and management strategies for PCOS, with a focus on lifestyle modifications and medical treatments. The article also discusses the potential complications and risks associated with the condition.